The influence of the video assistant referee on the UEFA European Championship - Bao, R.; Gómez Ruano, M. Á.; Shi, R.; Wang, X.; Han, B. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Video Assistant Referee (VAR) as a high-tech aid was introduced into football in 2018 to enhance the officiating accuracy of referees. At the 2020 UEFA European Championship, VAR was used for the first time. This study aims to investigate the impact of VAR on the UEFA European Championship.